Clinical laboratory medicine - McClatchey, Kenneth D.; Weinberg, Ruth W. (Editor); Reter, Raymond E.; Lerner, Mark (Doody's all reviewed collection., 2002)
Recommended in the Brandon/Hill selected list of print books and journals for the small medical library - April 2003 This thoroughly updated Second Edition of Clinical Laboratory Medicine provides the most complete, current, and clinically oriented information in the field. The text features over 70 chapters (seven new to this edition), including medical laboratory ethics, point-of-care testing, bone marrow transplantation, and specimen testing--providing comprehensive coverage of contemporary laboratory medicine. Sections on molecular diagnostics, cytogenetics, and laboratory management plus.